Vanadium Pentoxide Nanorods Deposited By Spray Pyrolysis Method For Photodetector And Ph Sensor Applications - Abdulghafor, Nabeel Mohammed (2017)
This research examines the growth of the V2O5 nanorods (NRs) by using spray pyrolysis method, and then fabricates photodetector with pH-EGFET sensor devices based on the V2O5 NRs. In addition the surface morphology, structural, and optical properties of the V2O5 NRs were studied. In the beginning, the V2O5 NRs growth was studied onto two substrates, silicon and glass. After which, the influence of substrate temperature, solution concentration, and deposition rate on the physical properties of the V2O5 NRs were examined.